Observed Relationships Between Sudden Stratospheric Warmings and European Climate Extremes. Issue 24 (27th December 2019) - King, Andrew D.; Butler, Amy H.; Jucker, Martin; Earl, Nick O.; Rudeva, Irina
Abstract: Sudden stratospheric warmings (SSWs) have been linked with anomalously cold temperatures at the surface in the middle to high latitudes of the Northern Hemisphere as climatological westerly winds in the stratosphere tend to weaken and turn easterly. However, previous studies have largely relied on reanalyses and model simulations to infer the role of SSWs on surface climate and SSW relationships with extremes have not been fully analyzed. Here, we use observed daily gridded temperature and precipitation data over Europe to comprehensively examine the response of climate extremes to the occurrence of SSWs. We show that for much of Scandinavia, winters with SSWs are on average at least 1 °C cooler, but the coldest day and night of winter is on average at least 2 °C colder than in non‐SSW winters. Anomalously high pressure over Scandinavia reduces precipitation on the northern Atlantic coast but increases overall rainfall and the number of wet days in southern Europe. In the 60 days after SSWs, cold extremes are more intense over Scandinavia with anomalously high pressure and drier conditions prevailing. Over southern Europe there is a tendency toward lower pressure, increased precipitation and more wet days. The surface response in cold temperature extremes over northwest Europe to the 2018 SSW was stronger than observed for any SSW during 1979–2016. Our analysis shows that SSWs have an effect not only on mean climate but also extremes over much of Europe. Only with carefully designed analyses are the relationships between SSWs and climate means and extremes detectable above synoptic‐scale variability. Plain Language Summary: Sudden stratospheric warmings (SSWs) are rapid warming events that occur tens of kilometers above the Earth's surface in the Northern Hemisphere. They are often associated with cold winter weather at the surface in the Northern Hemisphere, but previously, the connection between SSWs and cold extremes has been made using reanalyses and models rather than observational data. We performed the first comprehensive analysis of the link between SSWs and climate extremes in Europe. We found that winters with SSWs are substantially colder than average in areas like Scandinavia. Below‐average temperatures tend to precede SSW events, but the intensity of cold extremes, such as the coldest night of the month, tends to be strongest after the SSW event. Precipitation tends to decrease in northern Europe in winters with SSWs, but in southern Europe the aftermath of an SSW is often associated with more precipitation and an above‐average number of wet days. The 2018 SSW, for which the subsequent surface cold event was referred to as "The Beast from the East, " exhibited stronger cold anomalies in extreme indices over northwest Europe than any SSW in the 1979–2016 period. Through this analysis we found a link between SSWs and European wintertime climate extremes. Key Points: Using gridded observational surface data, we find a link between SSWs and European climate means and extremes Cooler average temperatures precede SSWs over much of northern Europe, but the intensity of cold extremes is greater after SSWs Methodological design has a large effect on the apparent strength of relationship between SSWs and European climate